Breaking Twitter : Elon Musk and the most controversial corporate takeover in history - Mezrich, Ben, 1969- (Grand Central, 2023)
From New York Times bestselling author Ben Mezrich: the book Elon Musk doesn't want you to read. Breaking Twitter takes readers inside the darkly comic battle between one of the most intriguing, polarizing, influential men of our time--Elon Musk--and the company that represents our culture's dearest hope for a shared global conversation. From employee accounts within Twitter headquarters to the mission-driven team Musk surrounded himself with, this is the full story from all sides. Can Musk miraculously succeed or will he spectacularly fail? What will that mean to the global town hall that is Twitter? What, really, is Elon's end goal? The whole world is watching. Breaking Twitter will provide ringside seats. Elon Musk didn't break Twitter. Twitter broke Elon Musk.